IMPROVING THE ABILITY OF MIDWIVES TO PREPARE FOR A SAFE AND COMFORTABLE BIRTH THROUGH PRENATAL YOGA - Setiyarini, Anggraini Dyah; Dewinataningtyas, Candra; Rahmawati, Erna; Andini, Dwi Margareta; Khalifatunnisak, Alfadefi; Andarini, Anna Septina; Nugraha, Nareswari Diska; Putri, Herdian Fitria Widyanto; Dewi, Ayu Rosita; Farokah, Atik; Putri, Ellatyas Rahmawati Tejo; Soyanita, Elin; Meritasari, Pety; Wulandari, Umianita Risca; Kumalasari, Dian; Yanuar, Dika; Ashari, Mia (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Anxiety, frequent urination, back pain, swollen feet, shortness of breath, and groin ache are just a few of the physical and mental changes that a pregnant woman may encounter. Yoga during pregnancy can help women feel less uncomfortable. To avoid trauma and ensure that the yoga poses are performed correctly, pregnant women who practice pregnancy yoga must be accompanied by a qualified facilitator. Thus, the purpose of this community service project was to improve midwives' prenatal yoga knowledge and proficiency. It is intended that by organizing this community service event, midwives would be able to assist in the local adoption of prenatal yoga. In order to complete this community service project, 23 midwives received training at the Comoro Health Centre in Dili, Timor Leste. The training took place from May 6 to 8, 2024 and was implemented in cooperation with the Comoro Health Centre. Activity technique: The midwife completes a form with multiple prenatal yoga-related questions before receiving the material (pre-test). Then, the material is provided, and prenatal yoga practice continues. Finally, the training participants are given additional questions (post-test) to determine whether their understanding of the prenatal yoga material has increased. Zoom media is used to do community service projects online. Results: A p value of 0.001 < 0.05 was achieved from the Wilcoxon statistical test used to measure pre and post knowledge levels. In summary: Midwives' understanding of prenatal yoga is effectively increased through community service that offers health education. Following the completion of this service, it is anticipated that the Comoro Health Center's midwives would be able to use the knowledge they have acquired to assist pregnant patients in their workplace.